Ikaros Zinc Finger Transcription Factors: Regulators of Cytokine Signaling Pathways and CD4+ T Helper Cell Differentiation - Powell, Michael D.; Read, Kaitlin A.; Sreekumar, Bharath K.; Oestreich, Kenneth J. (Frontiers in Immunology, 2019)
CD4+ T helper cells are capable of differentiating into a number of effector subsets that perform diverse functions during adaptive immune responses. The differentiation of each of these subsets is governed, in large part, by environmental cytokine signals and the subsequent activation of downstream, cell-intrinsic transcription factor networks. Ikaros zinc finger (IkZF) transcription factors are known regulators of immune cell development, including that of CD4+ T cell subsets. Over the past decade, members of the IkZF family have also been implicated in the differentiation and function of individual T helper cell subsets, including T helper 1 (TH1), TH2, TH17, T follicular (TFH), and T regulatory (TREG) cells. Now, an increasing body of literature suggests that the distinct cell-specific cytokine environments responsible for the development of each subset result in differential expression of IkZF factors across T helper populations. Intriguingly, recent studies suggest that IkZF members influence T helper subset differentiation in a feed-forward fashion through the regulation of these same cytokine-signaling pathways. Here, we review the increasingly prominent role for IkZF transcription factors in the differentiation of effector CD4+ T helper cell subsets.